Metabolomics: V1 data processing pipeline - Chien, Chi-Ming; Yu, Bruce; Watkins, Steve; Brinkley, Sarah (2025)
The Periodic Table of Food Initiative has developed distributable standardized protocols for sample preparation and nontargeted metabolomics data acquisition. Following data acquisition, laboratories upload their raw data to a data portal for standardized processing and annotation. This document describes the first generation (V1) of the data analysis method.